Directive Principles as Instruments of Social Transformation: Evaluating the Implementation of Socio-Economic Justice under Article 39 of the Indian Constitution - Babu Singh Rattan (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The Directive Principles of State Policy enshrined in Part IV of the Constitution of India represent a transformative constitutional mandate aimed at restructuring society on the principles of justice, equality, and human dignity. Among these, Article 39 occupies a pivotal position as it specifically directs the State to ensure equitable distribution of material resources, prevent concentration of wealth, secure adequate means of livelihood, promote equal pay for equal work, and protect vulnerable sections such as workers and children from exploitation. This paper critically examines Article 39 as an instrument of social transformation by evaluating its role in advancing socio-economic justice within the Indian constitutional framework. The study analyses the constitutional philosophy underlying Article 39 and assesses its implementation through legislative measures, judicial interpretation, and policy initiatives adopted by the State. It explores how welfare legislation, labor laws, land reforms, and redistributive policies have been shaped by the objectives of Article 39, while also highlighting the challenges and limitations that hinder its effective realization. Special emphasis is placed on the judiciary’s role in interpreting Fundamental Rights in the light of Article 39, thereby reinforcing the constitutional commitment to distributive justice and social welfare. The paper argues that despite its non-justiciable nature, Article 39 has significantly influenced India’s socio-economic governance and continues to serve as a moral and policy compass for achieving an inclusive and equitable social order.